Extracorporeal abdominal massage may help prevent recurrent bile duct stones after endoscopic sphincterotomy - Uchida, Naohito; Hamaya, Sae; Tatsuta, Miwa; Nakatsu, Toshiaki (Endoscopy International Open, 2016)
Background and study aims: Endoscopic sphincterotomy (EST) is effective, but recurrent bile duct stones are a common late complication. Because there are still no effective therapies for preventing this complication, some patients have experienced bile duct stone recurrence many times. We describe herein a method of abdominal massage to treat patients with prior cholecystectomy who have experienced recurrence of bile duct stones.